Fully-Diverse Lattices from Ramified Cyclic Extensions of Prime Degree - Interlando, J. Carmelo; Andrade, Antonio A.; Malaxechebarr´ıa, Bego˜na Garc´ıa; Ferrari, Agnaldo J; de Ara´ujo, Robson R (Academic Publications, 2020)
Let p be an odd prime. Algebraic lattices of full diversity in dimension p are obtained from ramified cyclic extensions of degree p. The 3, 5, and 7-dimensional lattices are optimal with respect to sphere packing density and therefore are isometric to laminated lattices in those dimensions.
Keywords: cyclotomic fields; lattices; modulation diversity; packing density